PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2017-2018 - Fikri Haikal; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzed the level of academic integrity of class XI MA Muhammadiyah Pekanbaru. The formulation of the problem is how to describe the academic integrity of class XI MA Muhammadiyah Pekanbaru students? Thus this study aims to determine the description of the academic integrity of XI class MA Muhammadiyah Pekanbaru. The research design was descriptive. This type of research is qualitative. The research sample was determined as many as 20 students and 6 teachers MA Muhammadiyah Pekanbaru. The data were obtained by collecting interview and documentation techniques. The results of the analysis show that overall, academic integrity in class XI MA Muhammadiyah Pekanbaru is categorized as good. Where it can be seen from the results of the research that the integrity of the value of mutual trust in class XI MA Muhammadiyah Pekanbaru can be categorized as good, besides that the value of honesty, mutual respect and responsibility value in class XI MA Muhammadiyah Pekanbaru can be categorized as quite good, then regarding the value integrity justice where students have received justice well accompanied by appreciation for the assessment is important for the formation of trust between teachers and students so that it can make students highly valued. Keywords: Program Implementation, PMBRW